2021
DOI: 10.1111/are.15379
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Acanthopanax senticosus extracts modulated the inflammatory and apoptotic responses of yellow catfish to protect against Edwardsiella ictaluri infection

Abstract: Herbal extracts interfere with bacterial adhesion and support apoptosis-dependent exfoliation to protect mammals against bacterial infection. In this study, juvenile yellow catfish were fed with control diet or Acanthopanax senticosus extracts (AS)supplemented diet. After 60 days, AS (180 ml/kg feed) significantly elevated fish growth and feed utilization, with higher weight gain and feed efficiency. After challenged with Edwardsiella ictaluri, survival rate of AS-supplemented fish (65%) was significantly high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…The expression level of JAK1 was significantly increased and then decreased compared to the control group. The results showed that CHMM may upregulate JAK1 expression, and with an increase in the dose of CHMM, specific cell types and conditions may cause JAK1 to be inhibited ( 54 ). Meanwhile, SOCS2 expression was significantly diminished compared to that of the control.…”
Section: Discussionmentioning
confidence: 99%
“…The expression level of JAK1 was significantly increased and then decreased compared to the control group. The results showed that CHMM may upregulate JAK1 expression, and with an increase in the dose of CHMM, specific cell types and conditions may cause JAK1 to be inhibited ( 54 ). Meanwhile, SOCS2 expression was significantly diminished compared to that of the control.…”
Section: Discussionmentioning
confidence: 99%
“…Chinese herbal medicines are rich in a variety of nutritional elements and biologically active substances, which can promote the synthesis of proteins and enzymes, accelerate the absorption and use of nutrients, stimulate the metabolism of animals, and thus be beneficial to animal growth [43,44]. In recent years, AS has been proven to play an active role in the growth of animals, such as yellow catfish (Pelteobagrus fulvidraco) [45], swamp eels (Monopterus albus) [46], weaned piglets [26], and broiler chickens [47]. In this study, we found that adding 0.4-0.8‰ ASW to the diet significantly promoted the growth of GIFT, and that 0.74‰ of ASW was the optimum concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Genes involved in the JAK-STAT signaling pathway have been identified in fish and also significantly affected by nutrients such as choline [ 74 ]. Our previous study also identified the regulatory role of the JAK-STAT signaling pathway on fish apoptosis during bacterial infection, which could be affected by herbal extracts [ 94 ]. In the present study, the expression of related genes including jak1 and stat5 were significantly increased at 30 d after F. columnare infection, while dietary glutamine supplementation significantly decreased their expression at 30 d. Thus glutamine might inhibit the JAK-STAT signaling pathway to decrease the apoptosis in fish gills after bacterial infection.…”
Section: Discussionmentioning
confidence: 99%